Multiplex touchdown polymerase chain reaction for rapid detection of Salmonella enterica subsp. enterica serovars Enteritidis and Typhimurium in food - Sandrasaigaran, P.; Kuan, C. H.; Son, R.; Gobal, D.; Abidin, U. F. U. Z.; Rukayadi, Y.; Hasan, H. (Rynnye Lyan Resources, 2023)
The Salmonella outbreak is one of the leading foodborne diseases in the world with increasing cases being reported annually. However, the current methods for Salmonella detection in foods are outdated, laborious and time-consuming. This necessitated developing a technique that is rapid for Salmonella detection in foods. Thus, the current study aimed to develop a multiplex touchdown PCR (m-TdPCR) protocol for rapid and simultaneous detection of Salmonella enterica subsp. enterica serovars Enteritidis and Typhimurium in foods. A two-phase m-TdPCR protocol was developed and optimized with primer pairs targeting the Salmonella enterica subsp. enterica (ST11/ST15-0.15 µM), serovars Enteritidis (sdfI gene-1.2 µM), Typhimurium (fliC gene-1.5 µM) and an internal amplification control (16S rRNA-0.08 µM). It was found that the m-TdPCR protocol is highly sensitive detecting up to 1 ng of Salmonella DNA and its specificity was verified using the in-silico method. Furthermore, the developed m-TdPCR shows no non-specific PCR amplicons and is able to detect both S. enterica ser. Enteritidis and S. enterica ser. Typhimurium in real-time when tested against the artificially contaminated food samples at up to 10-3 dilutions. Therefore, the validated m-TdPCR protocol in this study can be used as a tool for rapid detection of S. enterica ser. Enteritidis and S. enterica ser. Typhimurium in food samples and this may significantly reduce any related foodborne incidences in future. © 2023 The Authors. Published by Rynnye Lyan Resources.